MENYEMAI DEMOKRASI PADA MAHASISWA PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (STUDI ATAS PEMBELAJARAN CIVIC EDUCATION DI IAIN SURAKARTA - Muhammad Munadi (Jurnal Pendidikan Kewarganegaraan, 2019)
This study aims at investigating students’ responses of the assignments done outside the classroom. The responses were revealed through the way the students deliver their aspiration in a public institution. This study employs both quantitative and qualitative methods. The samples of the study are 34 students of Islamic Education Department (PAI) who attend Civic Education class. The data were collected using  questionnaire, observation and document analysis. The researcher used statistical and qualitative analysis. The results of the study show that: the assignments done outside the classroom through the delivery of the aspiration in the public institutions are responded on the average of 3.4, the interviews to the people who are directly involved in the democracy struggle is on the average of 3.2, and the observation to the people who are directly involved in the democracy struggle is on the average of 3.02. Qualitatively: the delivery of aspiration about the regional problems, the problems occurred around the students’ neighborhood,  were done through print media by sending short message service to Solopos newspaper and private FM Radio.Kata kunci: democracy; Islamic higher education; civic education